Analysis of Observational Characteristics of Extra-Large Hail in Shandong Peninsula on 1 October 2021 - Shasha Sun; Yi Sun; Chengfang Yang; Xiuguang Diao; Bohua Ren; Hui Guan (Advances in Meteorology)
Based on observational data, ERA5 hourly reanalysis data, and s-band dual-polarization radar data, the extremely severe convective weather happening in Shandong Peninsula on 1 October 2021 is analyzed. The results show that the process was affected by the upper-level cold vortex, and extremely severe convective weather happened from west to east in the northern area of Shandong Peninsula. Extra-large hail occurred in this process. The upper-level cold vortex provided the synoptic-scale dynamic forcing and unstable thermal stratification conditions, which were conducive to the occurrence of severe convective weather. About 2400 J · kg−1 sufficient convective available potential energy (CAPE) and 30.2 m · s−1 strong vertical wind shear between 0 and 6 km altitude prompted this severe convective weather to arise in October. Due to the special coastal geographical environment of Shandong Peninsula, the surface sea-breeze front triggered this severe convection process, and the movement of the surface convergence line stimulated the occurrence and development of convection nearby upstream and downstream. The three-body scatter spike (TBSS) and bounded weak echo region (BWER) of the storm were very significant. The value of ZDR is lower below 0°C layer than that above 0°C layer; meanwhile, the values of CC and KDP are higher below 0°C layer than that above 0°C layer. There were two ZDR columns on the east and west sides in the supercell storm, and the height (HT) of the east ZDR column top exceeds that of the −20°C layer. The thickness of the east ZDR column (about 3.2 km) was thicker than that of the west ZDR column (about 2.2 km). These all indicate that the storm had a deep updraft, which was conducive to the formation and growth of hail. There were also two KDP columns on the east and west sides of the BWER, which had almost the same thickness about 3.2 km, and both extended beyond the HT of the −20°C layer. The thickness of the strong reflectivity above 65 dBZ reaches 7 km, and the thickness of the ZDR column and KDP column reaches 2–3 km can be used as a reference for predicting extra-large hail in autumn short-term forecasting.